Analisis Perbedaan Abnormal Return, Trading Volume Activity dan Market Capitalization Sebelum dan Sesudah Pengumuman Covid-19 di Indonesia (Studi Peristiwa Pada Indeks Idx30) - Arsy Nasrulloh; Novi Khoiriawati (Universitas Batanghari Jambi, 2023)
President Joko Widodo officially released information on the entry of Covid-19 on March 2, 2020, in Indonesia. As a result, the Jakarta Composite Index ended lower at 5,361.25. The purpose of this study was to compare average abnormal return, trading volume activity, market capitalization of the IDX30 index before and after the announcement of Covid-19 in Indonesia. This research uses quantitative methods, and the approach in this research is an event study. The sampling technique used is saturated sampling; namely, all issuer companies included in the IDX30 index are 30 companies. Hypothesis testing uses the paired sample t-test for standard data and the Wilcoxon-signed rank test for abnormal data. Based on the findings of this study, there was no change between the average abnormal return and trading volume activity in Indonesia before and after the release of Covid-19. However, this study shows an average difference in market capitalization before and after the announcement of COVID-19